Averaging of Neumann problems for nonlinear elliptic equations in regions of framework type with thin channels - Kovalevskii, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The $G$-convergence of operators of the Neumann problem is established in regions with framework-type periodic structure with thin channels. A representation of the coefficients of a $G$-limiting operator is obtained.